Chloramphenicol or ceftriaxone, or both, as treatment for meningitis in developing countries?. Issue 6 (1st June 2003) - Duke, T; Michael, A; Mokela, D; Wal, T; Reeder, J
Abstract : Aims: To determine in children with meningitis whether there is any difference in mortality and neurological sequelae using chloramphenicol as first line treatment, with a change to ceftriaxone if chloramphenicol resistance is shown in vitro, compared to using ceftriaxone as first line treatment, with a change to chloramphenicol if there is no evidence of in vitro resistance. Methods: An observational study with a retrospective control group nested within a randomised trial of fluid management for bacterial meningitis where clinical care was standardised. Chloramphenicol is standard treatment for bacterial meningitis in Papua New Guinea. In the first 150 cases we used chloramphenicol and only changed treatment to ceftriaxone if chloramphenicol resistance for cerebrospinal fluid isolates was proved. After finding 20% of Haemophilus influenzae were resistant to chloramphenicol, and that most affected children had poor outcomes, we changed to an alternative strategy. In the next 196 cases first line treatment was ceftriaxone and treatment was changed to chloramphenicol if the isolated bacteria were found to be susceptible. Results: When chloramphenicol was used as first line treatment for meningitis followed by ceftriaxone when in vitro resistance was shown, there was invariably a very poor outcome in chloramphenicol resistant disease (71% of children died or had severe neurological complications). Using ceftriaxone as first line treatment was effective in reducing mortality and neurological sequelae from chloramphenicol resistant Haemophilus influenzae type (71% v 9%, relative risk 0.13; 95% CI 0.02 to 0.87; p = 0.013). Changing to chloramphenicol if there was no evidence of in vitro resistance was less than half the cost of empirical use of ceftriaxone for a full course for all children with meningitis. Conclusions: Using a third generation cephalosporin as first line treatment is effective in dealing with the problem of poor outcomes from meningitis due to Haemophilus influenzae that is resistant to chloramphenicol, and a strategy of changing to chloramphenicol if in vitro susceptibility is shown will reduce the use of expensive third generation cephalosporins without comprising on clinical outcomes. This highlights the urgent need to reduce the costs of third generation cephalosporins, to improve bacteriological services in developing countries, and to introduce effective and affordable vaccines against H influenzae and Streptococcus pneumoniae .